Proses Asuhan Gizi Terstandar melalui Pemberian Diet Tinggi Kalori Tinggi Protein dengan Alergi pada Pasien Bronchopneumonia: Laporan Kasus (Studi di RS X Kota Surabaya) - Dwi Mei Ayu Lestari (Media Gizi Kesmas, 2024)
potential to trigger allergic reactions that can increase mucus production, a standardized nutrition care process is carried out by providing a High-Calorie High-Protein diet (HCHP) with Allergies. Objectives: To implement a standardized nutritional care process and providing a HCHP-Allergy diet in bronchopneumonia patients. Methods: The case study was conducted on patients who were in the inpatient room of X Surabaya Hospital in October 2022. Samples were taken from the patient's medical records that had been approved by the duty nurse and accompanied by a hospital nutritionist. The method used was observation for 3 days on the aspect of intake with 24-hour food recall and visual comstock, physical aspects by interviews, and biochemical aspects seen through medical records. Results: After nutritional care, the patient's food intake for 3 days was still inadequate, which had not reached 90-110% of the needs, but the patient got food intake from outside the hospital, in the form of bread and milk. In addition, the patient also got interventions in the form of education related to the diet given. Conclusion: The patient's nutritional intake was still inadequate because the patient felt bored with the menu given, so it was necessary to evaluate the hospital’s food menu with the HCHP-Allergy diet.